2012
DOI: 10.1016/j.cej.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Biomass accumulation in a biofilter treating toluene at high loads – Part 1: Experimental performance from inoculation to clogging

Abstract: Biomass accumulation was studied in a biofilter packed with an organic/inorganic, hybrid packing material made of clay pellets plus clay pellets covered by a thin layer of compost and inoculated with activated sludge from a municipal WWTP. Operating conditions under high loads of toluene were selected to force plant failure by clogging. The biofilter achieved a remarkably maximum elimination capacity of 595 g toluene •m-3 •h-1 (1280 g toluene•m-3 •h-1 based on the first 25 cm of the biofilter). The evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…A mineral medium solution (prepared according to [32]) was supplied to the reactor using glucose as carbon source. The hydraulic residence time ranged from 4 to 8 hours throughout the FPB operation.…”
Section: Growth Of An Aerobic Biofilmmentioning
confidence: 99%
“…A mineral medium solution (prepared according to [32]) was supplied to the reactor using glucose as carbon source. The hydraulic residence time ranged from 4 to 8 hours throughout the FPB operation.…”
Section: Growth Of An Aerobic Biofilmmentioning
confidence: 99%
“…A peristaltic pump (MCP Standard, Ismatec, Germany) was used to feed the reactor with a nutrient solution (Dorado et al 2012) containing glucose as the sole carbon and energy source at 13 g·l -1 , and a second peristaltic pump (Miniplus 3, Gilson, France) served to recirculating the liquid phase through the reactor.…”
Section: Development Of An Aerobic Heterotrophic Biofilmmentioning
confidence: 99%
“…Since toluene is an organic material much less soluble in water, its concentration after this layer varied not as much as that of acetone. Removal efficiency of pollutants from cleaned air depends on gas residence time in biofilters (AlvarezHornos et al, 2007;Dorado et al 2008Dorado et al , 2010Dorado et al , 2012aGracy et al, 2006;Hwang and Tang, 1997;Jeong at al., 2006;Qi, 2005;Yoon and Park, 2002;Zilli et al, 2001). The longer is the empty bed residence time (EBRT) of polluted gas the higher removal efficiency can be observed.…”
Section: Cpeczasopismapanpl; Degruytercom/view/j/cpementioning
confidence: 99%
“…Dorado et al (2012a) found that biomass accumulation in a biofilter was enhanced by the high toluene load, particle size of the material, and its spatial distribution in the bed enabled to collect information on biomass growth. The results of their experiments demonstrated that high loads of toluene can be treated by a non-specific consortium in biofiltration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation